2009
DOI: 10.1088/0953-8984/21/5/055801
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian damping of Rabi oscillations in semiconductor quantum dots

Abstract: A systematic investigation is performed on the damping of Rabi oscillations induced by an external electromagnetic field interacting with a two-level semiconductor system. We have considered a coherently driven two-level system coupled to a dephasing reservoir and shown that, to explain the dependence of the dephasing rate on the driving intensity, it is essential to consider the non-Markovian character of the reservoir. Moreover, we have demonstrated that intensity-dependent damping may be induced by various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Under the similar assumption of the factorized initial system-reservoir density matrix state and the use of Eq. (7), the second-order time-convolutionless master equation in the interaction picture can be obtained as [6,7,[25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Derivations Of Evolution Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the similar assumption of the factorized initial system-reservoir density matrix state and the use of Eq. (7), the second-order time-convolutionless master equation in the interaction picture can be obtained as [6,7,[25][26][27][28][29][30][31][32][33][34][35][36] …”
Section: Derivations Of Evolution Equationsmentioning
confidence: 99%
“…(8) [6,7,[25][26][27][28][29][30][31][32][33][34][35][36]. One may be tempted to think that the second-order time-nonlocal master equation (8) is more accurate than the second-order time-local (time-convolutionless) master equation (9) since besides the Born approximation, the (first) Markovian approximation of replacingρ(t ′ ) withρ(t) in Eq.…”
Section: Derivations Of Evolution Equationsmentioning
confidence: 99%
“…The experimental resonance fluorescence spectra in QDcavities is similar to the characteristic Mollow triplet of an atomic system, but the sidebands of the triplet are found to undergo systematic spectral sideband broadening with increasing continuous-wave (cw) drives 19 . This drive-dependent broadening results from the interaction of the driven QD with the underlying phonon reservoir [22][23][24][25][26][27] . For cavity-QED (quantum electrodynamics) systems, acoustic phonon scattering processes also introduce an additional coupling mechanism between a cavity mode and the exciton 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…For the trion and donor-bound exciton heating of the electronic ensemble in the ground state is also one of the relevant mechanisms [30]. Nevertheless, it has been shown that the concrete mechanism is less important than the non-Markovian behavior of a reservoir [31,32]. Here, we assume that for our conditions the intensity-dependence of the dephasing rate is governed by excitation-induced dephasing (EID) [20,21].…”
Section: Pacs Numbersmentioning
confidence: 99%